A Wolf in Sheep's Clothing?: Jovan Rašković, the Serbian Democratic Party, and the "Serbian Question" in Croatia. (February 2017) - Hayball, Harry Jack
Jovan Rašković, the popular founding president of Croatia's Serbian Democratic Party (Srpska demokratska stranka, SDS), is widely viewed as representing a "missed opportunity" for peace in Croatia in 1990–1991, a moderate advocate of "cultural autonomy" and equality within Croatia who was undermined by the aggressive politics of Slobodan Milošević's Serbia, which supported instead the territorial and separatist ideas of Milan Babić. This support is considered a key component of Milošević's intervention in Croatia and is often viewed as decisive in foreclosing opportunities for a peaceful settlement of Croat–Serb relations. This article challenges this interpretation, arguing that the SDS's politics were premised from the start on the notion that the Serbs in Croatia were a "sovereign nation" with the right to self-determination up to secession. If Croatia remained in a Yugoslav federation, this meant that Serbs could opt for a wide variety of rights within Croatia, including forms of territorial autonomy. In the event of Yugoslavia's disintegration or transformation into a confederation, the Serbian minority could secede from Croatia. The differences between Rašković and Babić have been considerably overstated, and some of the SDS's more moderate rhetoric fundamentally misunderstood. It was Rašković, not Babić or Milošević, who founded the territorial and separatist politics of the Serbian Democratic Party in Croatia.